Perspektywy dialogu Kościoła katolickiego z Żydami w świetle synagogalnych przemówień Benedykta XVI - Ignatowski, Grzegorz (Śląskie Studia Historyczno-Teologiczne, 2011)
There are some researchers and journalists who claim that Benedict XVI is not favourably disposed to the Catholic-Jewish dialogue. The analyses of Pope’s speeches given in the Jewish synagogues, in Cologne – 2005, in New York – 2008 and in Rome – 2010, show that Benedict XVI not only encourages Catholics and Jews to the constructive dialogue but also points out to the questions which have to be deeply examined during the meetings and conversations. The first one is the problem of the common history and the second one is the theological relations between the Church and the Jewish people after the coming of Jesus Christ. To those issues that have not been unresolved he adds also the necessity of the discussion the moral contemporary problems, especially the Decalogue Commandments.